Post-Fermentation Preservation of Shidal- a Fermented Fish Product of North-East India - P., Mahanta; A.U., Muzaddadi (Fishery Technology, 2025)
Shidal is a popular traditional semi-fermented fish product exclusively prepared from Puntius spp. Being a salt free product, it has short storage life outside the mutka (earthen pot) and thus traditionally preserved either by dusting with common salt during retailing or by keeping it inside mutka until sold in the market. Present study was conducted to develop a low cost packing and preservation method for shidal outside mutka using different concentrations of salt in glass bottles. Shidal was packed in glass bottles after sprinkling with salt (2% and 5%) and stored at ambient temperature (18-340C) for 120 days. Parameters related to microbial, biochemical and sensory changes were analyzed at 15 day intervals from August to December 2010 and the quality was compared with the control (without salting) to see the periodic quality loss. The 2% salt treated shidal (T1) showed comparatively stable pH (4.6 to 4.8) with negligible variation throughout the storage period while in control and 5% salt treated shidal (T2), pH increased significantly (P<0.05) after 75 days of storage and reached 7.09 from an initial pH of 4.4. Moisture, ash, salt, protein and fat content of all the samples did not vary significantly (P>0.05) during the storage period upto 60 days indicating insignificant effects by the treatments on proximate composition. All the parameters increased significantly (P<0.05) during storage in all the samples indicating hydrolysis and degradation of protein. But the treated samples had slower rate of increments in the non-protein nitrogen, free Ã¡-amino nitrogen and total volatile base nitrogen compared to the control. Similarly, the peroxide value, free fatty acid and thiobarbituric acid showed slower rate of increments and insignificant changes in the treated samples than in the control. Total plate count did not change significantly (P>0.05) and remained near 7 Log cfu g-1. Total fungal count was low in almost Â all samples. The sensory scores indicated longer shelf life of 90 days for T1 and T2 while the control had shelf life of 60 days in glass bottles.